Iconic Native Culture Cues Inhibit Second Language Production in a Non-immigrant Population: Evidence from Bengali-English Bilinguals - Roychoudhuri, Kesaban S.; Prasad, Seema G.; Mishra, Ramesh K. (Frontiers in Psychology, 2016)
We examined if iconic pictures belonging to one's native culture interfere with second language production in bilinguals in an object naming task. Bengali-English bilinguals named pictures in both L1 and L2 against iconic cultural images representing Bengali culture or neutral images. Participants named in both "Blocked" and "Mixed" language conditions. In both conditions, participants were significantly slower in naming in English when the background was an iconic Bengali culture picture than a neutral image. These data suggest that native language culture cues lead to activation of the L1 lexicon that competed against L2 words creating an interference. These results provide further support to earlier observations where such culture related interference has been observed in bilingual language production. We discuss the results in the context of cultural influence on the psycholinguistic processes in bilingual object naming.